1997
DOI: 10.1021/ci960151e
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of Large Databases of Compounds:  Using the MDL “Keys” as Structural Descriptors

Abstract: An analysis of chemical structures from several commercially available libraries of compounds is presented with a view of acquiring compounds for screening. The Jarvis−Patrick clustering method has been applied, using the MDL “keys” as structural descriptors. The nature of the MDL keys is examined in this context, some features of the clustering algorithm are discussed, and clustering statistics are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
176
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(179 citation statements)
references
References 13 publications
2
176
1
Order By: Relevance
“…The ISIS keys are small topological substructure fragments, whereas the MACCS keys consist of the ISIS keys plus algorithmically generated more abstract atom-pair descriptors. MDL keys are commonly used when optimizing diversity (McGregor and Pallai, 1997;Roberto Todeschini, 2010). For example, the PubChem data base uses a fingerprint that is 881 bits long to rank substances against a query compound.…”
Section: A Molecular Descriptors/featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The ISIS keys are small topological substructure fragments, whereas the MACCS keys consist of the ISIS keys plus algorithmically generated more abstract atom-pair descriptors. MDL keys are commonly used when optimizing diversity (McGregor and Pallai, 1997;Roberto Todeschini, 2010). For example, the PubChem data base uses a fingerprint that is 881 bits long to rank substances against a query compound.…”
Section: A Molecular Descriptors/featuresmentioning
confidence: 99%
“…Two structures cluster together if they are in each other's list of nearest neighbors, and they have at least K of their J nearest neighbors in common. The MDL keys also provide a way to eliminate compounds that are least likely to satisfy the drug-likeness criterion (McGregor and Pallai, 1997).…”
Section: B Molecular Fingerprint and Similarity Searchesmentioning
confidence: 99%
“…This molecular fingerprint uses a pre-defined set of definitions and creates molecular fingerprints based on pattern matching of the structure to the defined "key" set. 4) This key based approach relies on the definitions to encapsulate the molecular descriptions. The keys were originally developed for the purpose of database substructure searching.…”
Section: Methodsmentioning
confidence: 99%
“…14,21 It has been shown that this method performs well for chemical clustering and is computationally efficient for large databases. 17,22 rEsults…”
Section: Methodsmentioning
confidence: 99%